Aggregating Service Level Agreements in Services Bundling: A Semiring-Based Approach - Nguyen, Trung-Viet; Lê, Lam-Son; Nguyen-An, Khuong (Future Data and Security Engineering, 2016)
Business services arguably play a central role in service-based information systems as they fill in the gap between the technicality of Service-Oriented Architecture and the business aspects captured in Enterprise Architecture. Business services have distinctive features that are not typically observed in Web services, e.g. significant portions of the functionality of business services might be executed in a human-mediated fashion. As such, service level agreement (SLA) should be described as a mixture of human-mediated functionality (e.g., service penalty) and computer-interpretable measurement (e.g., reliability, payment). In this paper, we propose a formal framework for reasoning about the SLAs from the perspective of services bundling – the practice of innovatively organizing business services into a bulkier service offering that creates new values. Specifically, we (a) represent multi-level SLA of a business service in terms of service reliability, payment and penalty using the mathematical structure of semiring; (b) provide formality for aggregating SLAs of the constituent services that make up the service bundling; (c) make multi-level SLAs of a bundled service technically comparable. The main contribution of this work is a machinery for handling a large number of SLAs generated through services bundling, allowing to the service consumers to pick up the right service offering according to their preference.